Motion Graphics Video as Learning Media to Improve the Empathy of Preschool Children - Karisya Aprilliani; Lulu Mamluatul Adibah; Lulu Zulfa Akyuni; Sulistia Rahayu Khoerunnisa; Jihan Nurul Afifah; Jojor Renta Maranatha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT. The purpose of this study was to find out how much influence the use of Motion Graphics Video learning media has on the empathy of preschool children. The method used in this study is a quasi-experimental method with a pretest-posttest control group design. This research was conducted in a kindergarten located in Purwakarta, Indonesia. The participants involved in this study were children aged 5-6 years (group B) totaling 15 children from the UPI Purwakarta Lab school as an experimental class and 15 children from Mentari Kindergarten as a control class. The rating scale carried out in this study aims to determine the empathy of children aged 5-6 years before being given treatment and after being given treatment through pretest and posttest. Furthermore, the data were analyzed using a paired simple t-test to determine the effect of learning methods on the empathy of preschool children, and an independent sample t-test to determine the difference in empathy between the experimental group and the control group. The results of this study are (1) There is an influence of motion graphic video learning media on the empathy of preschool children. (2) There is a difference in empathy between preschool children who learn using motion graphics video media with preschool children who learn using big book media. The conclusion obtained from this study is that motion media graphic video is more effective than conventional media (big book) in increasing empathy for preschool-age children. Keywords : Motion Graphics Video, Empathy, Early Childhood